Hubungan Motivasi Berprestasi Matematika Dan Kemampuan Spasial Siswa Sekolah Dasar: Indonesia - Nurhafizah; Gustimal Witri; M. Jaya Adi Putra (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the relationship between achievement motivation and spatial abilities of elementary school (SD) students. This type of research is a quantitative study with a correlation research method. This research was conducted at SD Negeri 004 Rokan with a population of 219 people and a sample of 97 people. This sample was taken from classes IV, V, and VI. The instrument used was a closed questionnaire using a Likert scale and test questions. The results showed that the achievement motivation of elementary school students can be categorized as moderate with a percentage of 87.62% or amounting to 85 students out of 97 students. High category with a percentage of 7.21% or amounting to 7 students from 97 students. Low category with a percentage of 5.15% or amounting to 5 students out of 97 students. The level of spatial ability of elementary school students can be categorized as the medium with a percentage of 64.04% or amounting to 66 students out of 97 students. Evidenced by the results of data analysis, the relationship between achievement motivation and students' spatial abilities obtained rHitung equal to 0.22 which indicates that the relationship is in a low category.